Relationship Between Lifestyle Habits and Health-Related Quality of Life of Recently Diagnosed Breast Cancer Patients: A Comparison Between Younger and Older Women in China - Zheng, Chao; Yu, Li-Xiang; Jia, Hong-Ying; Cui, Shu-De; Tian, Fu-Guo; Fan, Zhi-Min; Geng, Cui-Zhi; Cao, Xu-Chen; Yang, Zhen-Lin; Wang, Xiang; Liang, Hong; Wang, Shu; et al. (Frontiers in Public Health, 2021)
Objective: The aim of the study was to evaluate the relationship between lifestyle habits and health-related quality of life (HRQoL) among different ages who were initially diagnosed with breast cancer (within the first two weeks) and determine the contribution of lifestyle habits factors on HRQoL. Methods: A multi-center, hospital-based, case control study was conducted among breast cancer women from 22 hospitals in 11 provinces or municipalities in China. The FACT-B was used to measure HRQoL. Chi-square test, ANOVA and multivariable generalized linear models were conducted to identify differences in HRQoL between two age groups (age <50 years and ≥50 years) and to evaluate the contribution of lifestyle habits factors on HRQoL of breast cancer patients. Results: 1199 eligible breast cancer patients were used for analysis. Younger women (age <50 years) appeared to show lower scores than older women (age ≥50 years) in HRQoL subscales including emotional well being (p=0.003), functional well being (p=0.006), breast cancer subscale (p=0.038), and FACT-B Total scores (p=0.028). Tea and alcohol consumption, very satisfied with sleep and current life were the strongest predictors of higher HRQoL in younger group. Meanwhile, no coffee consumption, frequent participation in physical activities, high sleep satisfaction and current life satisfaction were the key predictors of higher HRQoL in older breast cancer women. Conclusion: The relationship of the nine lifestyle habit items to HRQoL were different between younger and older women. Associated variable of low HRQoL can help clinicians take intervention early in order to improve the prognosis of breast cancer patients.